Testing and manufacturing with numerical modeling of metal PTB orthosis - M.Abbas, Saif; Qasim Humadi, Rasha; M. Takhakh, Ayad (International Journal of Engineering and Technology, 2019)
In this work, fiber glass as a reinforcement in composite material used for manufacturing ankle foot orthoses (AFO) PTB type of metal valve with vacuum molding technique fabricated. The material was depended on 8 layers of fiber glass. The mechanical properties of the AFOsâ€™ material were studied by tensile test, and fatigue test. The results showed that the tensile strength (Ï¬ult ) for fiber glass are 224 MPa, yield strength (Ï¬y ) was 170 MPa and elongation at break 1.9mm.The gait cycle (ground reaction force (GRF)) and pressure distribution data were collected by using force plate and F-socket devices respectively for patient of age 29 years with height 185cm and weight 83kg .Heel contact time percent without PTBO equal to 5%, when wearing fiber glass PTBO equal to 59%. The midstance time percent for patient without PTBO equal to 12% when wearing PTBO equal to 34%. Solid work software program was used for PTPO modeling Also; the FEM (ANSYS ver.18.2) was used to compute the equivalent stress (Von-Mises), safety factor of fatigue and total deformation for fiber glass PTBO model. The obtained results from ANSYS gave the profile of safety factor of fatigue (1.1492).Â Â